Geographical proximity vs network tie: innovation of equipment manufacturing firms in Shanghai, China - Lin, Lan; Wang, Fenglong (ERDKUNDE, 2019)
Recent theoretical arguments and empirical studies in economic geography have emphasized the importance of both geographical proximity and network tie for firm innovation. However, few studies have empirically assessed the effects of these two together. This paper examines and compares the effects of geographical proximity and network tie on innovation based on a unique dataset of equipment manufacturing firms in Shanghai, China. An extended spatial economic model is adopted for this analysis. We find evidence that network ties rather than geographical proximity promote firm innovation. This finding is different from previous studies using region as unit of analysis and suggests that geography and network may play different roles at different spatial scales. Moreover, we demonstrate that both internal factors such as firm’s expenditures on R&D and human capital and external factors such as government expenditure on R&D and import of foreign technologies are important for innovation of Chinese equipment manufacturing firms.